Can macroeconomists get rich forecasting exchange rates? - Mauro Costantini; Jesus Crespo Cuaresma; Jaroslava Hlouskova (Institute for Advanced Studies (IHS), 2014)
We provide a systematic comparison of the out-of-sample forecasts based on multivariate macroeconomic models and forecast combinations for the euro against the US dollar, the British pound, the Swiss franc and the Japanese yen. We use profit maximization measures based on directional accuracy and trading strategies in addition to standard loss minimization measures. When comparing predictive accuracy and profit measures, data snooping bias free tests are used. The results indicate that forecast combinations help to improve over benchmark trading strategies for the exchange rate against the US dollar and the British pound, although the excess return per unit of deviation is limited. For the euro against the Swiss franc or the Japanese yen, no evidence of generalized improvement in profit measures over the benchmark is found.
Keywords: C53; F31; F37; 330; exchange rate forecasting; forecast combination; multivariate time series models; profitability